TARA ZAHRA, The Great Departure: Mass Migration from Eastern Europe and the Making of the Free World, New York 2016, W. W. Norton & Company, 392 pp., IBSN 978-0-393-07801-5 - Herza, Filip (Dějiny – teorie – kritika, 2018)
Book review